2014
DOI: 10.1093/nar/gku705
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of hnRNPK negatively modulates apoptosis upon DNA damage through local regulation of phosphorylation

Abstract: Heterogeneous nuclear ribonucleoprotein K (hnRNPK) is an RNA/DNA-binding protein involved in chromatin remodeling, RNA processing and the DNA damage response. In addition, increased hnRNPK expression has been associated with tumor development and progression. A variety of post-translational modifications of hnRNPK have been identified and shown to regulate hnRNPK function, including phosphorylation, ubiquitination, sumoylation and methylation. However, the functional significance of hnRNPK arginine methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 71 publications
3
51
0
Order By: Relevance
“…The methylation of p53 at the Lys372 residue induces acetylation at adjacent lysine residues, resulting in activation of p53 transcriptional activity (30). In addition, protein methylation regulates phosphorylation (31, 32). Arginine methylation of the DNA/RNA-binding protein heterogeneous nuclear ribonucleoprotein K inhibits its phosphorylation by PKCδ, resulting in enhancement of heterogeneous nuclear ribonucleoprotein K–mediated cell apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylation of p53 at the Lys372 residue induces acetylation at adjacent lysine residues, resulting in activation of p53 transcriptional activity (30). In addition, protein methylation regulates phosphorylation (31, 32). Arginine methylation of the DNA/RNA-binding protein heterogeneous nuclear ribonucleoprotein K inhibits its phosphorylation by PKCδ, resulting in enhancement of heterogeneous nuclear ribonucleoprotein K–mediated cell apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, protein methylation regulates phosphorylation (31, 32). Arginine methylation of the DNA/RNA-binding protein heterogeneous nuclear ribonucleoprotein K inhibits its phosphorylation by PKCδ, resulting in enhancement of heterogeneous nuclear ribonucleoprotein K–mediated cell apoptosis (31). Furthermore, PRMT1-mediated arginine methylation of Axin induces its phosphorylation by glycogen synthase kinase 3 β, leading to decreased ubiquitination and subsequent stabilization of Axin (32).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation and arginine methylation are often mutually exclusive [e.g. (55)], but arginine methylation can also promote phosphorylation (56). Proteins detected in the phosphoproteome of tachyzoites are enriched in genes that are up-regulated at several time points during cell cycle, including mid-G1 phase (27).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, it is not clear what arginine residues within CIITA are targeted by PRMT1. In addition, it remains undetermined whether PRMT1-induced CIITA degradation is solely a result of PRMT1-dependent arginine methylation or a secondary effect contingent on communications with other types of post-translational modifications since PRMT1-dependent arginine methylation has been shown to form crosstalk with acetylation2627, ubiquitination2829, and phosphorylation3031. It has been previously shown that CIITA poly-ubiquitination plays a role in regulating its stability20, although CIITA mono-ubiquitination could enhance its activity without altering its half-life32.…”
Section: Discussionmentioning
confidence: 99%